2017
DOI: 10.1007/s12603-017-0891-6
|View full text |Cite
|
Sign up to set email alerts
|

Disability in the individual ADL, IADL, and mobility among older adults: A prospective cohort study

Abstract: Older adults were mostly disabled in physical related activities, whereas disability in more cognitive related activities was less often experienced. The impact of multimorbidity on disability in each activity was substantial, while education was not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
69
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 36 publications
11
69
0
2
Order By: Relevance
“…For instance, Brian and his colleagues [16] found that older Puerto Rican adults with comorbid diabetes and depressive symptoms were prone to developing ADL disability and mortality. Su et al [3] found that among Chinese community-dwelling elderly people, multimorbidity (comorbid with chronic diseases) was significantly associated with ADL and IADL impairment; similar findings were also observed in a study conducted in Netherlands [17].Studies have recently found that social capital, which reflects how individuals or groups can get resources by their inter-social networks and support, has substantial influence on elderly health [18]. The role of social capital in living arrangements [19], mental health [20], and life satisfaction was observed among elderly people from previous studies in China [21].…”
supporting
confidence: 66%
See 1 more Smart Citation
“…For instance, Brian and his colleagues [16] found that older Puerto Rican adults with comorbid diabetes and depressive symptoms were prone to developing ADL disability and mortality. Su et al [3] found that among Chinese community-dwelling elderly people, multimorbidity (comorbid with chronic diseases) was significantly associated with ADL and IADL impairment; similar findings were also observed in a study conducted in Netherlands [17].Studies have recently found that social capital, which reflects how individuals or groups can get resources by their inter-social networks and support, has substantial influence on elderly health [18]. The role of social capital in living arrangements [19], mental health [20], and life satisfaction was observed among elderly people from previous studies in China [21].…”
supporting
confidence: 66%
“…For instance, Brian and his colleagues [16] found that older Puerto Rican adults with comorbid diabetes and depressive symptoms were prone to developing ADL disability and mortality. Su et al [3] found that among Chinese community-dwelling elderly people, multimorbidity (comorbid with chronic diseases) was significantly associated with ADL and IADL impairment; similar findings were also observed in a study conducted in Netherlands [17].…”
supporting
confidence: 63%
“…Bleijenberg et al 19 investigated a prospective Dutch cohort regarding its performance in 15 activities, and found that the advanced ones, which demand a proper physical execution -e.g., traveling -, declined sooner than ADLs, while difficulties with IADLs, which require cognitive abilities -e.g., using the telephone, taking medicines, and managing finances -, developed later than with ADLs -e.g., bathing/showering, dressing, and transferring.…”
Section: Discussionmentioning
confidence: 99%
“…The physical components of disability are found to increase with age and are commonly diagnosed by self-reporting. Objectively, disability can be identified using instruments measuring activities of daily living (ADL) or instrumental activities of daily living (IADL) 22 . Disability can be seen as an outcome of frailty 19,23 .…”
Section: Multimorbidity Disability and Frailtymentioning
confidence: 99%